2008
DOI: 10.1007/s10165-008-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α inhibits chondrogenic differentiation of synovial fibroblasts through p38 mitogen activating protein kinase pathways

Abstract: We previously reported that synovial fibroblast-like cells (SFs) can be differentiated into chondrocytes through activin receptor-like kinase (ALK) 3 activation. The aim of this study was to clarify the effect and signaling pathways of tumor necrosis factor (TNF)-alpha on the chondrogenic differentiation of SFs. Primary SFs from patients with rheumatoid arthritis (RA) were treated with recombinant human bone morphogenetic protein-2 or transduced with a constitutively active mutant of the ALK3 gene (ALK3CA) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Therefore we confirm that ADSCs are another cell subset in which chondrogenic properties are suppressed by TNF. The chondrogenesis of BMSCs is inhibited by TNF in NF-kB-dependent manner [27] and the chondrogenic capacity of FLS is inhibited by TNF through p38 mitogen activating kinase pathways [29]. In the rheumatoid synovium, MSCs have impaired chondrogenic potential due to the inflammatory environment (partially composed of TNF), and a negative relationship between synovial MSC chondrogenic capacity and magnitude of synovitis has been reported [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we confirm that ADSCs are another cell subset in which chondrogenic properties are suppressed by TNF. The chondrogenesis of BMSCs is inhibited by TNF in NF-kB-dependent manner [27] and the chondrogenic capacity of FLS is inhibited by TNF through p38 mitogen activating kinase pathways [29]. In the rheumatoid synovium, MSCs have impaired chondrogenic potential due to the inflammatory environment (partially composed of TNF), and a negative relationship between synovial MSC chondrogenic capacity and magnitude of synovitis has been reported [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, up to a third of all TNF-induced genes in FLS are dependent on p38 MAPK signalling [17]. Not only does TNF contribute to destruction of bone and cartilage in RA [18-20], it also inhibits chondrocyte differentiation from FLS and neochondrogenesis [21]. p38 MAPK is implicated in the production of TNF, interleukin (IL)-1β and IL-6 amongst other inflammatory cytokines in the pathogenesis of RA (Table 2).…”
Section: Pathological Roles Of P38mapkmentioning
confidence: 99%
“…33 Since SDSCs are used to facilitate cartilage tissue regeneration, it is critical to consider the effect of synovitis on chondrogenic differentiation of OA SDSCs since inflammatory cytokines have previously been shown to inhibit chondrogenesis. 27,28 CD14 is a glycoprotein expressed on the surface of myelomonocytic cells as a GPI-anchored receptor or secreted in a soluble form. 34 We observed a correlation between IL-1b and TNF-a levels of synovial fluid and CD14 levels in osteoarthritic SDSCs.…”
Section: Cd14 and Proinflammatory Cytokines On Chondrogenesis In Oa Smentioning
confidence: 99%
“…It has been reported that TNF-a inhibits the chondrogenic differentiation of synovial fibroblasts through p38 mitogen-activated protein kinase pathways; NFkB-dependent inhibition by IL-1b and TNF-a of the chondrogenic differentiation of human bone marrow (BM) MSCs has also been reported. 27,28 To date, however, the direct function of these factors with respect to repression of chondrogenic differentiation has not been clearly elucidated.…”
mentioning
confidence: 99%